2015
DOI: 10.1158/1055-9965.epi-15-0212
|View full text |Cite
|
Sign up to set email alerts
|

Weight Change in Breast Cancer Survivors Compared to Cancer-Free Women: A Prospective Study in Women at Familial Risk of Breast Cancer

Abstract: Background This study prospectively examines weight gain in breast cancer (BC) survivors compared to cancer-free women from a familial risk cohort. Methods Absolute and percent weight change over 4 years was compared among 303 BC survivors and 307 cancer-free women matched on age and menopausal status, from the same familial risk cohort. Linear and logistic regression was used to estimate the association between survivor status and weight gain. Results Overall, BC survivors gained significantly more weight… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 44 publications
2
22
0
1
Order By: Relevance
“…Furthermore, only 35% of those whose consumption of fruit and vegetables was below recommendations reported eating more healthy foods after diagnosis, while less than a third of overweight or obese women reported increased efforts to maintain a healthy body weight. Previous reports have also suggested that many breast cancer survivors gain weight following treatment [17], and that survivors may experience greater weight gain than cancer-free women of the same age [24]. These findings, along with ours, demonstrate that although many women are motivated to make healthy changes following a breast cancer diagnosis, there is still room for improvement through dietary interventions and increased health promotion efforts.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, only 35% of those whose consumption of fruit and vegetables was below recommendations reported eating more healthy foods after diagnosis, while less than a third of overweight or obese women reported increased efforts to maintain a healthy body weight. Previous reports have also suggested that many breast cancer survivors gain weight following treatment [17], and that survivors may experience greater weight gain than cancer-free women of the same age [24]. These findings, along with ours, demonstrate that although many women are motivated to make healthy changes following a breast cancer diagnosis, there is still room for improvement through dietary interventions and increased health promotion efforts.…”
Section: Discussionsupporting
confidence: 79%
“…Although we examined changes in weight from before to after diagnosis in women with an incident breast cancer diagnosis, prior studies have recruited women with a prevalent breast cancer diagnosis, and focused their analyses on weight changes occurring in the postdiagnosis period. In the Breast and Ovarian Surveillance Service (BOSS) Cohort Study, prospective cohort of individuals with a familial risk of breast and/or ovarian cancer, significantly greater gains in self‐reported weight were observed in survivors of breast cancer (303 women) than age‐matched women without breast cancer (307 women) from the same cohort . However, to our knowledge, other studies, using either self‐reported or standardized measured weight, have reported no significant differences in postdiagnosis weight gain between survivors of breast cancer and age‐matched women without breast cancer.…”
Section: Discussionmentioning
confidence: 83%
“…Given the follow‐up period spanned more than a decade, it is reasonable to think the weight of some women may have changed from diagnosis. Moreover, weight gain during BC treatment is common . Some studies suggested weight gain after BC diagnosis was associated with worst prognosis, although another concluded that weight gain up to 4 years post‐diagnosis was not associated with a higher risk of death .…”
Section: Discussionmentioning
confidence: 99%